RELATIVE EFFICIENCIES OF DIFFERENT LIPIDS AND LIPID LEVELS IN THE DIET OF THE PRAWN PENAEUS INDICUS - Ali, S Ahmad (Indian Journal of Fisheries, 2011)
Among the four lipids, cod liver oil, prawn head oil, sardine oil and soybean lecithin, tested at 6% levelin a purified diet, for the prawn Penaeus indicus, the diets having prawn head oil and a mixed lipidconsisting of all the four lipids in equal proportions, showed significantly (P